The enhanced high-temperature oxidation resistance of additively manufactured GH4169 by adding small amounts of 304L - Yajing Li; Hailong Dai; Shuyao Zhang; Bo Li; Yunran Ma; Chengyu Bao; Xu Chen; Fuzhen Xuan (Journal of Materials Research and Technology, 2024)
Enhancing the high-temperature oxidation resistance of nickel-based alloys is critical for expanding their industrial applications. Herein, we report a novel strategy for enhancing the high-temperature oxidation resistance of the GH4169 nickel-based alloy by adding small amounts of 304L stainless steel using selective laser melting technology. The oxidation property of GH4169 with various 304L additions (2 wt.%, 4 wt.%, and 6 wt.%) at 900 °C for 45 h was investigated. Results show that the addition of 304L significantly improves the oxidation resistance of GH4169. The thickness of the oxide film and the intergranular oxidation depth of GH4169 with 6 wt.% 304L added are reduced by 61% and 69%, respectively. The addition of 304L increases Cr and decreases Ni in the matrix, which facilitates the formation of a more compact oxide film. The Nb in Laves phase will be increased with 304L addition, which effectively inhibits oxygen penetration and metallic element diffusion.